Two-step transition towards the reversibility region in Bi2Sr2CaCu2O8−δ single crystals - Pastoriza, H.; Cruz, F. de la; Mitzi, D.B.; Kapitulnik, A. (American Physical Society, 1992)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina